PENGARUH PROGAM PENGALAMAN LAPANGAN (PPL) TERHADAP KESIAPAN MENJADI GURU PADA MAHASISWA FKIP UNS ANGKATAN 2011 - Ariani, Rizki Putri; Martono, Trisno; Indriayu, MIntasih (Department of Economics Education, Universitas Sebelas Maret, 2015)
This research aims to determine whether there is influence of Teaching Practice Progam (TPP) toward the readiness to become teacher in college students of Social Science Education Study Program of FKIP UNS generation 2011. TPP activity can be interpreted as a training program for students to apply a range of knowledge, attitudes, and skills in order to prepare the establishment of a professional teacher. This research is descriptive quantitative research with survey method.The population in this research is students’ college of Social Science Education Study Program of FKIP UNS generation 2011 that have followed PPL number of 414 students. The sample in this research amounted to 81 students were taken by using Proportional Random Sampling technique. The instrument was used a questionnaire and documentation. Data analysis techniques were used to test the hypothesis is the analysis of simple regression analysis. The results of research showed there was a positive and significant effect of Teaching Practice Progam (TPP) (X) on the readiness become a teacher (Y) in the students’ college of Social Science Education Study Program of FKIP UNS.